Superovulatory response and embryo production potential of Jakhrana goats treated with porcine follicle stimulating hormone - GOEL, A K; KHARCHE, S D; JINDAL, S K; SINHA, N K (The Indian Journal of Animal Reproduction, 2005)
Six regularly cycling adult Jakhrana goats were superovulated during mid to late luteal phase of oestrous cycle by administering 16 mg FSH-P (Sigma Laboratories , USA) 1/M in reducing dose schedule over a period of 3 days at 12 hours interval. Oestrus was synchronized by using Lutalyse (Dinoprost trometharnine, Upjohn, USA) @7.5 mg 1/M per goat or½ Crestar implant (Norgestomet +Oestradiol V alerate Intervet, Holland). Goats exhibiting oestrus after treatment were naturally bred at the onset of oestrus and 12 hours later. Each responded goat received hCG (Chorulon, Intervet, Holland) @ 500 IU IN 10-12 hours after the onset of synchronized oestrus to enhance ovulatory rate. Five of six (83.33%) goats responded to oestrus synchronizing treatments within 24-36 hours (average 31.20±2.62 hrs.) of treatment withdrawal and stayed in oestrus for 24 - 48 hours (average 31.20±4.29 hrs). Responders were subjected to mid-ventral laparotomy after 74-84 hours of oestrus onset to flush embryos from oviducts. Average ovarian response and transferable embryo recovery were 9.40±2.53 and 5.20±2.71, respectively. One donor showed exceptionally good embryo recovery of 17 embryos. Unruptured follicles averaged 5.40±1.34. Recovered embryos were transferred in 5 recipients and remaining were used for freezing. Study revealed the feasibility of using this technique to enhance kidding rate in this unexplored goat breed.